Análisis de flujo vehicular en las intersecciones semaforizada de las principales avenidas del centro de la ciudad de santa rosa. - Tigre Saca, Kerly Fabiola (2017)
The great increase of vehicular volume that exists at present is due to the growth of the inhabitants in the cities and the necessity of transport is a transit with itself in the ways, that produce problems and the discomfort in the population, project of road construction or renovation of road, among others, it is necessary to carry out an analysis of the elements of vehicular flow in the area a project the road project, reason why in this report is an analysis realized in the different intersections semaphores of the center of the city of Santa Rosa, knowing that the main objective is to analyze the level of service provided by the road, characteristics and behavior of the vehicular volume in the city of Santa Rosa, due to this a manual traffic count is performed at the traffic lights intersections of the city center of Santa Rosa, which three are three, placed around the park Sucre like son, the Av. Gral. Eloy Alfaro that contains with l intersections, Av. Antonio Jose de Sucre and Av. Cristóbal Colon and the third intersection conformed by Av Libertad and Av. Simón Bolívar, which was realized during six days of the week counting from the day Monday to the day Saturday from 7:00 a.m. to 4:00 p.m., the counting manual will check the behavior of the vehicles, which increased at the beginning and at the end of the week, due to the beginning and closing of the work of the inhabitants of the city, taking into account that instantly to carry out the study it was possible to verify that part of the avenue Antonio Jose de Sucre is a closed part and also part of the Avenue Cristóbal Colón which intercepts the way General Eloy Alfaro reason why it makes difficult the citizens and the study of these pathways, so that are untransited roads and therefore unused traffic lights and therefore an analysis that can not use a future because in a short period of time it reopens, at the time of the completion of the work renewal of the Santa Rosa GAD road. No large number of traffic lights in the city were found. The data were taken at the intersections available to carry out the respective project. In order to select the studies that are carried out to define the service levels of the avenues, before choosing the methodology is applied, so we proceeded to perform a systematic observation for the analysis of traffic flow by a count, reading all the bibliographical researches found, it was possible to choose how to work on this project, for it was carried out three studies a manual counting base of vehicles, which are Transit TPDA, Synchro 8, transit simulator and HCM 1985 1985 with the help of Excel the results could be obtained, with which we can see the number of mixed vehicles that transit in a day, for each direction of rotation of the avenues, realizing the TPDA, with the method of HCM 1985 and program of Syncrho 8, simulator of transit, we will obtain the levels of service of each way. .